SIMULASI GETARAN PADA RODA DAYA YANG DIDUKUNG BANTALAN MAGNET PERMANEN - Djill Van Itrantoi; Michael Rembet; Stenly Tangkuman (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2021)
Object such as Fly Wheel, it is bound to have natural frequency as one of it is vibration parameter. If excitation is applied at the same frequency as natural frequency, then resonance will occur. As the result, excess deformation on the structure can occur. In this research, the natural frequency from the Fly Wheel was calculated. The calculation was conducted with the help of Finite Element on a software. Followed with the calculation of the working frequency range and structure deformation as a result of the vibration that occurred. The deformation calculation was conducted because deformation will effect the size (dimension) between the wheel and the housing.Â However, the simulation that was conducted only on the first five vibration mode.Â This Research is consisted of four stages. The four stages are literature study, fn analysis of a basic road, preliminary measurement mechanical battery and fn analysis of the mechanical battery. Preliminary measurement was conducted because the mechanical battery that was analysed is already constructed in Construction Laboratory, Department of Mechanical Engineering, University of Sam Ratulangi.The Result of the simulation indicated that five vibration mode occurred on these spinning frequency are 32.21 Hz, 88.71 Hz, 173.93 Hz, 287.48 Hz, and 429.32 Hz. Followed, the biggest working range are between vibration mode two to three. Finally, deformation that effected the size between Fly Wheel and housing bearing it is on two, three and five.Key Words: Fly Wheel, Natural Frequency, Vibration Simulation with Software.